Conflict in neighbouring (developing) countries: Direct and indirect effects on economic growth - Fatmata Lovetta Sesay (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Conflicts in developing countries have been known to cause havoc well over the borders within which they are fought. A recurring question is to measure the externalities arising from niehgbour's conflict. Specifically, this paper looks at the effects of conflict in one country, on the economic growth of its neighbours but also the effect on growth enhancing variables. The empirical analyses include 72 countries, 40 from sub-Sahara Africa, 4 from North Africa and 14 from Asia and Latin America respectively. Using data from the 'States in Armed Conflict Report 2000', the empirical relationship between the existence and duration of conflict in developing countries and economic growth of its neighbours is confirmed. The study uses standard methods of panel data estimation (fixed effects and random effects), which makes it possible to control for time-invariant country-specific effects. The study finds that conflict in one country does not only reduce economic growth of its neighbours but also significantly affects other growth enhancing variables. The main policy implication of the study is that the resolution of conflict should take a regional perspective since costs arising from conflict spread over several countries in the neighbourhood. And also post conflict reconstruction should take these costs into account to avoid further conflicts within the region.
Keywords: 330; Wirtschaftswachstum; Schätzung; Entwicklungsländer; Politischer Konflikt